2015
DOI: 10.1038/tpj.2015.52
|View full text |Cite
|
Sign up to set email alerts
|

Carboplatin/taxane-induced gastrointestinal toxicity: a pharmacogenomics study on the SCOTROC1 trial

Abstract: Carboplatin/taxane combination is first-line therapy for ovarian cancer. However, patients can encounter treatment delays, impaired quality of life, even death because of chemotherapy-induced gastrointestinal (GI) toxicity. A candidate gene study was conducted to assess potential association of genetic variants with GI toxicity in 808 patients who received carboplatin/taxane in the Scottish Randomized Trial in Ovarian Cancer 1 (SCOTROC1). Patients were randomized into discovery and validation cohorts consistin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
0
8
0
2
Order By: Relevance
“…As for ATP7B , ATP7B rs9535828 A allele and rs9535826 G allele carriers had better treatment outcome of platinum‐based chemotherapy in NSCLC patients . In addition, ATP7B rs1061472 and rs1801249 were reported to be significantly associated with carboplatin/taxane‐induced gastrointestinal toxicity in ovarian cancer patients . These findings show that ATP7A and ATP7B may be potential biomarkers to predict the response to platinum‐based chemotherapy.…”
Section: Atp7a/7b and Platinum Drug Resistancementioning
confidence: 76%
See 1 more Smart Citation
“…As for ATP7B , ATP7B rs9535828 A allele and rs9535826 G allele carriers had better treatment outcome of platinum‐based chemotherapy in NSCLC patients . In addition, ATP7B rs1061472 and rs1801249 were reported to be significantly associated with carboplatin/taxane‐induced gastrointestinal toxicity in ovarian cancer patients . These findings show that ATP7A and ATP7B may be potential biomarkers to predict the response to platinum‐based chemotherapy.…”
Section: Atp7a/7b and Platinum Drug Resistancementioning
confidence: 76%
“…ATP7A rs2227291 was found to be associated with cisplatin resistance in epithelial ovarian cancer patients (44). However, no ATP7A polymorphisms were observed to be associated with carboplatin/taxane-induced gastrointestinal toxicities in ovarian cancer patients (45). As for ATP7B, ATP7B rs9535828 A allele and rs9535826 G allele carriers had better treatment outcome of platinum-based chemotherapy in NSCLC patients (46).…”
Section: Atp7a/7b and Platinum Drug Resistancementioning
confidence: 97%
“…It has been shown that single nucleotide polymorphisms (SNPs) might affect gene expression and function, accounting for interindividual differences in drug efficacy and toxicity 18 , 19 . A few ATP7B SNPs have been reported possible role in chemotherapeutic toxicity 20 , 21 . However, less is known about the effects of SNPs on the expression level of ATP7B and the response to platinum-based chemotherapy in NSCLC patients.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, patients with advanced OVCA develop recurrent disease and die within 5 years due to development of resistance to platinum‐based chemotherapy (Raja et al, ). In addition, standard platinum–taxane doublet chemotherapy is associated with several adverse side effects including gastrointestinal toxicity (He et al, ), febrile neutropenia and peripheral neuropathy (Wang et al, ), and other non‐hematological toxicities (Shawky et al, ).…”
mentioning
confidence: 99%